Vitalitas Bahasa Bima di Kota Balikpapan: Analisis Faktor Pergeseran dan Pemertahanan - Anhar, Anhar; Ilmi, Nur (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study analyzes the vitality of Bima language among migrant communities in Balikpapan City through examining language shift and maintenance factors. Employing a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and documentation of the Bima community in RT 09, Sepinggan Raya Sub-district. Data analysis used the interactive analysis model of Miles and Huberman encompassing data reduction, data display, and conclusion drawing/verification. Research findings identified 17 data comprising 6 language shift data (immigration, economic, and education factors) and 11 language maintenance data (family, social interaction, communication intensity, activities, and desire factors). Results indicate that despite language shift occurring in formal domains (35.3%), language maintenance is more dominant (64.7%), particularly in family and intra-ethnic social domains. The geographical concentration of the Bima community (80%) creates a linguistic enclave supporting language vitality. This study concludes that Bima language demonstrates strong linguistic resilience through intergenerational transmission and language loyalty, though requiring systematic intervention for long-term sustainability as a manifestation of local cultural existence. As a recommendation, synergy is needed among families, communities, educational institutions, and local governments through the integration of Bima language into local curriculum content, digital-based language documentation, and the strengthening of community organizations to ensure language transmission to future generations